2002
DOI: 10.1016/s0008-6363(01)00443-6
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin induces desensitization of cardiac endothelin-1 receptor signaling by increased expression of RGS4 and RGS16

Abstract: These data suggest that the rapid up-regulation of cardiac RGS4 and RGS16 is associated with a desensitization of endothelin-1 receptor signaling. Up-regulation of these RGS proteins may thus be involved in the early onset of cardiac failure during sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…Again, mRNA expression of RGS16 was up-regulated by LPS exposure whereas RGS2, RGS3, RGS4 and RGS5 expression levels were also unaffected. These data are in line with the reported transient increase in RGS16 mRNA and protein expression in rat hearts and cultured neonatal cardiomyocytes after LPS treatment (21). Also in pig heart and aorta an up-regulation of RGS16 mRNA expression upon LPS exposure has been described (19).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Again, mRNA expression of RGS16 was up-regulated by LPS exposure whereas RGS2, RGS3, RGS4 and RGS5 expression levels were also unaffected. These data are in line with the reported transient increase in RGS16 mRNA and protein expression in rat hearts and cultured neonatal cardiomyocytes after LPS treatment (21). Also in pig heart and aorta an up-regulation of RGS16 mRNA expression upon LPS exposure has been described (19).…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have suggested a role for RGS4 and RGS16 in the early onset of cardiac failure during septic shock (21). Probably, alterations in RGS protein expression also play a role in the hypotension associated with LPS treatment and the hypo-responsiveness of several vasoconstrictors.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We have previously carried out a degenerate RT-PCR screen in the hearts of a porcine model of sepsis and have thus identified both RGS1 and RGS16 as being upregulated [168]. Similarly, Wieland's group found that R4 RGSs, including RGS16 and RGS4 were upregulated in the septic heart [70,169]. They further demonstrated that overexpression of RGS16 was sufficient to attenuate endothelin-1 signalling in the heart.…”
Section: Altered Rgs Expression Is Associated With Pathophysiologicalmentioning
confidence: 95%
“…RGS4 plays an important role in promoting cardiac development, regulating neuronal plasticity, and modulating smooth muscle contraction (2). In cardiomyocytes, RGS4 expression is induced by endotoxin and interleukin (IL)-1␤ (57,58) and contributes to the loss of G␣ q -mediated activation of phospholipase C (PLC) by endothelin-1 (51). In the central nervous system, RGS4 is linked to schizophrenia (6,14,27,44,46), Alzheimer disease (13), and Huntington disease (63).…”
mentioning
confidence: 99%